Experimental Analysis of Diurnal Variations in Humic-Like Fluorescent Dissolved Organic Matter in Surface Seawater - Omori, Yuko; Saeki, Akira; Wada, Shigeki; Inagaki, Yuji; Hama, Takeo (Frontiers in Marine Science, 2020)
Humic-like fluorescent dissolved organic matter (FDOM) have been widely used as tracers for bio-refractory dissolved organic matter to understand its dynamics in the oceans. Vertical distributions of humic-like FDOM are controlled by microbial production in the ocean interiors and photobleaching in surface layers. Although humic-like FDOM is expected to be actively produced in surface layers with high bacterial activity, its production in surface seawater is not well understood. To examine the diurnal variations in humic-like FDOM due to microbial production and photobleaching in surface seawater, we conducted seven experiments from night to day using surface seawater in the subtropical Pacific and coastal regions. Parallel factor analysis determined that FDOM in the incubated seawater was composed of three components: two types of humic-like FDOM and a protein-like FDOM. The fluorescence intensity of humic-like FDOM increased to 104.0 ± 2.5% of the initial intensity during the night and decreased to 101.2 ± 2.5% under sunlight exposure during the day. Conversely, its intensity significantly increased to 114.0 ± 2.7% under dark conditions during the day. The turnover rates of humic-like FDOM by the increase and decrease in its intensity were estimated to be 0.14 and 0.11 d–1, respectively. These comparable turnover rates indicated that the production and photobleaching of humic-like FDOM were almost in equilibrium in the surface layer, with a low level of humic-like FDOM. Linear correlations between the intensity of humic-like FDOM and concentrations of dissolved oxygen in all experiments under dark conditions indicated that humic-like FDOM were produced as the by-products of microbial respiration processes in the surface seawater. Using global bacterial respiration rates, the net production rate of humic-like FDOM in the global photic layer was estimated as 4.2–5.5 x 1017 R.U. yr–1, contributing to 75% of its production in the entire ocean.